Prevalence of depression and anxiety in patients with cystic fibrosis and parent caregivers: results of The International Depression Epidemiological Study across nine countries - Quittner, Alexandra L; Goldbeck, Lutz; Abbott, Janice; Duff, Alistair; Lambrecht, Patrick; Solé, Amparo; Tibosch, Marijke M; Bergsten Brucefors, Agneta; Yüksel, Hasan; Catastini, Paola; Blackwell, Laura; Barker, Dave (Thorax, 2014)
Individuals with chronic diseases and parent caregivers are at increased risk for symptoms of depression and anxiety. Prevalence of psychological symptoms was evaluated in adolescents and adults with cystic fibrosis (CF) and parent caregivers across nine countries. Patients with CF, ages 12 years and older, and caregivers of children with CF, birth to18 years of age, completed measures of depression and anxiety across 154 CF centres in Europe and the USA. Psychological symptoms were compared across countries using χ(2). Logistic regression examined extent of comorbid symptoms, predictors of depression and anxiety, and concordance between parent and adolescent symptomatology. Psychological symptoms were reported by 6088 patients with CF and 4102 parents. Elevated symptoms of depression were found in 10% of adolescents, 19% of adults, 37% of mothers and 31% of fathers. Elevations in anxiety were found in 22% of adolescents, 32% of adults, 48% of mothers and 36% of fathers. Overall, elevations were 2-3 times those of community samples. Participants reporting elevated anxiety were more likely to report depression (ORs: adolescents=14.97, adults=13.64, mothers=15.52, fathers=9.20). Significant differences in reports of depression and anxiety were found by patient age and parent respondent. Concordance between 1122 parent-teen dyads indicated that adolescents whose parents reported depression were more likely to be elevated on depression (OR=2.32). Similarly, adolescents whose parents reported anxiety were more likely to score in the elevated range on the anxiety measure (OR=2.22). Symptoms of depression and anxiety were elevated in both patients with CF and parents across several European countries and the USA. Annual screening of psychological symptoms is recommended for both patients and parents.